Factors Related to the Early Stage of Alcohol Drinking Among Male Students At Lower Secondary Schools, Bangnumprieo District, Chachoengsao Province - Khondok, Mantana; Homsin, Pornnapa; Srisuriyawet, Rungrat (วารสารสาธารณสุข มหาวิทยาลัยบูรพา, 2012)
The purposes of this study were to identify the prevalence of alcohol drinking and to examine factors related to the early alcohol drinking stage among lower secondary school male students. The participants were 424 lower secondary school male students in Bangnumprieo district, Chachoengsao province, selected by multistage sampling. Data were collected by questionnaires: demographic data, attitudes towards alcohol drinking, developmental assets, alcohol drinking. The consistency of the questionaires was analyzed using Cronbach alpha. Statistics used including mean, percentage, standard deviation, and binary logistic regression. The findings of the study showed that the prevalence of early stage alcohol drinking was 63.2%. The average age of first drink was 12.3 years old. Both protective factors and risk factors were associated with early alcohol drinking stage. These factors were religion (OR=4.01, 95% CI = 2.39 - 6.73), attitudes towards alcohol drinking (OR=1.94 , 95% CI = 1.21 - 3.12), community assets (OR=1.92, 95% CI = 1.08 - 3.41), access to alcoholic drinks (OR=1.90, 95% CI = 1.17 - 3.08), age (OR=1.99, 95% CI = 1.19 - 3.34), academic success (OR=1.89, 95% CI =. 1:15 - 3:10), family assets (OR=1.79, 95% CI = 1.01 - 3.17) and internal assets (OR=1.74 ,95% CI = 1.04 - 2.89). The results contribute to knowledge and understanding of risk factors and protective factors of alcohol drinking. It will be beneficial to nurses and health personnel to prevent and reduce risk factors of alcohol drinking among male adolescents.